The North Korea's Nuclear Threat: A Case Study of the Security Dilemma in East Asia - Ardiyanti, Dwi; Sinambela, Stivani Ismawira; Fitria, Nur Rahma (Resolusi: Jurnal Sosial Politik, 2024)
The purpose of this study is to analyze the security dilemma of this concept when examining East Asian states' responses to North Korea's nuclear weapons. It is a concept of international relations, which advocates a state in which one country strengthens its national security while reducing the security of another country. North Korea's claim that its nuclear program is self-defense is a security dilemma, but the sole threat to its neighbor is sparking a response from East Asian nations. Under the threat of North Korean nuclear weapons, East Asian countries choose to ensure national security by enhancing military capabilities and strengthening military alliances. The method used in this study is qualitative. The results of this study suggest that the concept of security dilemma is a concept that can describe the responses of East Asian countries to North Korea's security dilemma. Responses by regional states such as China, South Korea, and Japan have led to increased military capabilities to protect their own countries in an attempt to maintain superpower alliances. The analysis of the case study can be demonstrated by implementing the factor dynamic Asian map of the security dilemma process of the case study, the response of East Asian countries to North Korea's nuclear weapons.